CHRONIC PERIODONTITIS AND DISEASES INDUCED BY ATHEROSCLEROSIS - López-Ilisástigui, Alina (2016)
Objective: Correlate the presence of chronic periodontitis in patients with heart disease consequential of the atherosclerosis and agroup control without these manifestations. Materials and methods: The present cross-sectional descriptive study, developed in theDentistry Service of the Institute of Cardiology and Cardiovascular Surgery from La Habana (study group diagnosed with cardiovasculardisease consequent of atherosclerosis) and the consultation of the Periodontics Department from the Dental School from La Havana(control group, without this diagnosis), during the months of January to June of 2013. Those groups were comprised by 85 patientseach one, both sexes and between 35 and 70 years of age. The studied variables were age, sex, presence of periodontitis, periodontalattachment loss and risk factors for atherosclerosis. Results: A significant difference was found regarding the presence of chronicperiodontitis in both groups of patients